A Novel Multi-Neural Ensemble Approach for Cancer Diagnosis. Issue 1 (31st December 2022) - Gupta, Surbhi; Gupta, Manoj Kumar; Kumar, Rakesh
ABSTRACT: Cancer is a complex worldwide health concern that resulted in 10 million cancer deaths in 2018; hence, early cancer detection is crucial. Early detection involves developing more precise technology that offers information about the patient's cancer, allowing clinicians to make better-informed treatment options. This study provides an in-depth analysis of multiple cancers. This study also exhibits a good survey of the machine or deep learning techniques used in cancer research. Also, the study proposed a stacking-based multi-neural ensemble learning method's prediction performance on eight datasets, including the benchmark datasets like Wisconsin Breast cancer dataset, mesothelioma, cervical cancer, non-small cell lung cancer survival dataset, and prostate cancer dataset. This study also analyzes the three real-time cancer datasets (Lung, Ovarian & Leukemia) of the Jammu and Kashmir region. The simulation findings indicate that the methodology described in our study attained the highest level of prediction accuracy across all types of cancer data sets. Additionally, the proposed approach has been statistically validated. The purpose of this investigation was to develop and evaluate a prediction model that might be used as a biomarker for malignancy based on anthropometric, clinical, imaging, and gene data.